Thirty years of research on physical activity, mental health, and wellbeing: A scientometric analysis of hotspots and trends - Sabe, Michel; Chen, Chaomei; Sentissi, Othman; Deenik, Jeroen; Vancampfort, Davy; Firth, Joseph; Smith, Lee; Stubbs, Brendon; Rosenbaum, Simon; Schuch, Felipe Barreto; Solmi, Marco (Frontiers in Public Health, 2022)
The sheer volume of research publications on physical activity, mental health, and well-being is overwhelming. The aim of this study was to perform a broad-ranging scientometric analysis to evaluate key themes and trends over the past decades, informing future lines of research. We searched Web of Science Core Collection from inception until December 7th, 2021, using the appropriate search terms such as ‘physical activity’ or ‘mental health’, with no limitation of language or time. Eligible studies were articles, reviews, editorial material, and proceeding papers. We retrieved 55,353 documents published between 1905 and 2021. The annual scientific production is exponential with a mean annual growth rate of 6.8% since 1989. The 1988-2021 co-cited reference network identified 50 distinct clusters that presented significant modularity and silhouette scores indicating highly credible clusters (Q=0.848, S=0.939). This network identified 6 major research trends on physical activity, namely cardiovascular disease, somatic disorders, cognitive decline/dementia, mental illness, athletes’ performance, related health issues, and eating disorders, and the COVID-19 pandemic. A focus on the latest research trends found that greenness/urbanicity (2014), concussion/chronic traumatic encephalopathy (2015), and COVID-19 (2019) were the most active clusters of research. The USA research network was the most central, and the Chinese research network, although important in size, was relatively isolated. Our results strengthen and expand the central role of physical activity in public health, calling for systematic involvement of physical activity professionals as stakeholders in public health decision-making process.